The Cognitive Spectrum of Transformative Learning - Dix, Michael (Journal of transformative education, 2016)
Although different transformative learning theories have been described in the literature, a detailed integrative theory is yet to emerge. I argue that unduly intellectualist assumptions regarding cognition have hampered current understandings and have obscured transformative learning's cognitive and metacognitive essence. Firstly, Mezirow's implied restriction of his Socratic/Habermasian model to discursive rationality unnecessarily excludes transformative learning accomplished through enactive, non-discursive modes of cognition, metacognition, and rationality. Likewise, a narrow conception of cognition prevents theorists of depth transformation from recognising the essential cognitive roles at depth of metaphors deriving from embodied experience and their rational elaboration at depth through metaphoric implication. In the light of current theory, I reconsider J.H. Newman's nineteenth-century insights regarding notional-to-real transformation, showing how a deeper and more comprehensive understanding of cognition and metacognition reveals transformative learning's essential cognitive and metacognitive dynamic, in confirmation of Kegan's “subject-object” model and Mezirow's stress on the importance of metacognition.